191 Quality of Life Improvements in Persistent Asthma Subjects Receiving Combined Mometasone Furoate and Formoterol - Murphy, Kevin (World Allergy Organization Journal, 2012)
BACKGROUND: A major goal of asthma treatment is to improve patients' health-related quality of life (QoL). Mometasone furoate/formoterol (MF/F) combination therapy was recently approved for the treatment of persistent asthma. The objective of this analysis was to examine the effect of MF/F on health-related QoL at the approved doses. METHODS: Data from 2 phase III studies investigating the effects of MF/F 200/10 μg (study P04334) and MF/F 400/10 μg (study P04431) were included. All subjects were ≥12 yeara and not well controlled on medium dose (P04334) or high-dose (P04431) inhaled corticosteroid (ICS). After 2 to 3 weeks of run-in on twice-daily (BID) MF 200 μg (P04334) or 400 μg (P04431), subjects were randomized to 26 weeks of BID MF/F 200/10 μg, MF 200 μg, F 10 μg, or placebo (PBO) in P04334; or 12 weeks of BID MF/F 200/10 μg, MF/F 400/10 μg, or MF 400 μg in P04431. The Asthma Quality of Life Questionnaire with Standardized Activities (AQLQ [S]), consisting of 4 domains (Symptoms, Activity Limitation, Emotional Function, and Environmental Stimuli), was used to assess QoL. AQLQ(S) score changes from baseline were assessed; a difference ≥0.5 was considered clinically meaningful. Study protocols were approved by IRBs; written informed consent was provided by all subjects or a parent/guardian. RESULTS: In P04334 (n = 781), subjects receiving MF/F 200/10μg experienced significant improvements in total score (13.1%) and the 4 domain scores of the AQLQ (S) at endpoint vs those receiving PBO (P ≤ 0.005) or F 10 μg (P ≤ 0.024). Clinically meaningful improvements in total AQLQ (S) from baseline to week 26 were observed in patients receiving MF/F 200/10 μg (0.61). In P04431 (n = 728), subjects receiving MF/F 200/10 μg experienced significant improvements in total score (12.8%) and the Symptoms and Activity Limitation domain scores of the AQLQ (S) at endpoint vs those who received MF 400 μg (P ≤ 0.017). Clinically meaningful improvements in total AQLQ (S) from baseline to week 12 occurred in patients receiving MF/F 200/10 μg (0.61), MF/F 400/10 μg (0.51), or MF 400 μg (0.5). CONCLUSIONS: Patients with persistent asthma receiving MF/F had statistically significant, clinically meaningful improvements in QoL in 2 phase III studies. These data suggest that MF/F combination therapy improves the health-related QoL of patients with persistent asthma who are inadequately controlled on medium- or high-dose ICS.